Aggregate uncertainty and the supply of credit - Valencia, Fabián (Journal of Banking & Finance, 2017)
This paper presents a model in which a bank can exhibit self-insurance with loan supply contracting when uncertainty increases. This prediction is tested with U.S. commercial banks, where identification is achieved by looking at differential effects according to banks’ capital-to-assets ratio (CAR). Increases in uncertainty reduce the supply of credit, more so for banks with lower levels of CAR. These results are weaker for large banks, and are robust to controlling for monetary policy, to different measures of uncertainty, and to breaking the dataset in subsamples. Quantitatively, the effect of uncertainty shocks on credit supply is about as important as that of monetary policy shocks.